RI 5056 Portable Methane-Detecting Appliances Approved Under United States Bureau Of Mines Standard ? Introduction - E. J. Gleim (The National Institute for Occupational Safety and Health (NIOSH), 1954)
For many years mining men have sought for a portable device that would be direct reading and permit more positive detection of methane than was possible with flame safety lamps, which depended so largely on the training, skill, and personal ability of the user. Through the years, after the discovery that methane contributed to many mine explosions, considerable effort and large sums of money have been expended in searching for and developing instruments that would be practical, and, at the same time, reliable and safe to use. Very early in the history of the Bureau of Mines, some of its engineers were unsuccessful, after many trials, in attempts to develop such an instrument. Commercial firms, however, persisted in research until today a number of instruments are on the market that have proved to be practical in coal-mine service. It is hoped, however, that further research will bring about improvements in accuracy and other desirable features. BUREAU OF MINES STANDARD FOR METHANE DETECTORS The Bureau of Mines recognized the need for establishing minimum requirements on which to base official approval of suitable Instruments. This standard was prepared as Schedule 8. It was revised before being issued in printed form. The revision was published as Schedule 8A in 1920 and was revised on two other occasions. The present edition, known as Schedule BC, was issued October 31, 1935.